HUBUNGAN TAYANGAN KEKERASAN DI TELEVISI DENGAN PRESTASI BELAJAR SISWA DI SEKOLAH DASAR - Dewi Septiani Mandasari (Universitas PGRI Adi Buana Surabaya, 2018)
Each learning process will result in changes in the behavior of students who experience the process. For students in school schools, this moral and social coaching can be done through formal study, as well as elements that can continue and develop the soul and developing soul and spirit and value value 1945 to the younger generation should be improved in the curriculum and community environment. There are many things that can result in a child behaving to imitate what he has seen or seen. One of them is the violence in electronic or television media. Impressions of violence in teleisi can directly affect a child's behavior to imitate him because the child does not yet know what he or she is seeing is true or false. The hypothesis of this research is